Enabling Inclusion of Students with Visual Impairment at Higher Education level: Perspectives of Visually Impaired Students - Samina Ashraf, Muhammad Ishaq, (JIE, 2024)
Visualizing education for persons with visual impairment through a lens of inclusive education implies restructuring of academic institutions. This study was designed to examine the enabling features for the inclusion of students with visual impairment at the higher education level. The main objectives of the study were to explore the views of visually impaired students on enabling factors for their inclusion at higher education level, find out the difference among the views of students studying in different higher education institutions.